Corporatism and Economic Performance - Fredrik C. A. Andersson (Lund University, School of Economics and Management, Department of Economics, 2000)
This paper models corporatism as affecting both the preferences of the parties involved as well as the rules of the game. The analysis is conducted in a union-government game on determining wages and unemployment benefits. The result indicates that international conditions might be important for the functions of the concept of corporatism. It may also serve as an explanation to the poor performance on production and employment in some of the former so successful European corporatist states in the 1990s. The implication of this is that corporatism might not be a successful social organisation in the globalised economy.
Keywords: J32; J51; 330; Corporatism; Interest groups; Labour unions